LOOKING AT ALAWITES - Al-Tamimi, Aymenn Jawad (The Levantine Review, 2012)
This paper aims to provide some original discussion on the traditional Alawite religion, looking at current historical narratives of the Alawites during the French Mandate period in what in 1936 became the Syrian Republic. The paper also considers conceptions of identity in the modern era and perceptions of the Syrian civil war a Sunni-Shi’a conflict. Finally, it examines the position of Alawites in the current civil war in Syria, and discusses future options for the community.